Increasing Vaccine Uptake during Pregnancy by Using Prenatal Education Classes: An Effective Tool for Health Communication and Promotion - Stefania Triunfo; Silvia Perossini; Esther Burdin; Elena Claudia De Angeli; Maria Francesi; Alessandra Garolfi; Jessica Moretti; Ilenia Paruscio; Miriam Tassielli; Marta Tremolada; Simona Gemelli; Deborah Pedrina; et al. (MDPI AG, 2023)
Childbirth education classes represent an antenatal tool for supporting pregnant women and couples in increasing knowledge on pregnancy, delivery, breastfeeding, and newborn care. The aim of this study was to investigate the impact of an additional lesson during the prenatal course regarding the advantage of vaccination to mitigation of maternal anxiety. An observational study was designed that included participants in childbirth education classes and compared courses enhanced by the extra lesson on vaccination during pregnancy versus those who did not receive it. Assessment of the impact of prenatal educational on vaccination was measured by using validated questionnaires (State-Trait Anxiety Inventory, STAI; Perceived Stress Scale, PSS; World Health Organization- Five Well-Being Index, WHO-5). A total of 145 pregnant women participated to the investigation by answering to the online survey. Of them, 33 patients (22.8%) belonged to the course without a lesson on vaccine, while 112 (77.2%) participated to online prenatal education that included an additional meeting on the usefulness of getting vaccinated during pregnancy. No statistical differences were found between study groups in terms of demographics and perinatal outcomes. Participants in the enriched course reported lower basal anxiety levels than those without the vaccine lesson (STAI-State, normal score < 40, 30 vs. 19%, p-value 0.041; STAI-State, mild score 40-50, 78 vs. 67%, p-value 0.037). With reference to the prior two weeks, maternal wellbeing level was improved by the added class (score > 13 as measurement of wellbeing: 62% vs. 80%, p-value < 0.05). Moderate perceived stress assessed by PSS was found in those pregnant women without prenatal education on vaccination (64 vs. 50%, p-value 0.042). The introduction of a lesson regarding vaccination during pregnancy in the program of prenatal education courses improved maternal anxiety levels and wellbeing, in addition to reducing perceived stress.